An Interesting Study of Capacity Improvement of a Shipyard in Myanmar - Aung Ye Kyaw; Djauhar Manfaat; Buana Ma’ruf (Institut Teknologi Sepuluh Nopember, 2017)
Abstract¾ Six shipyards are in operation under control of Engineering Department of Inland Water Transport. Among them, Dalla shipyard currently accounts for about 50 percent of repair work on ships owned by the Inland Water Transport (IWT). The efficiency of the shipyard, which is about 164 years old, is hampered by old equipment, including some from the WWII-era (Word War II). Now the shipyard needs to be upgraded to improve its current capacity in ship repair. In this study, we proposed two ways which are supporting facilities and re-layout shipyard to increase ship repair. This paper obtains two alternative layouts of shipyard. The first alternative layout does not change the existing layout of shipyard but steel plate warehouse are built. The second alternative changes the existing layout because machine shop and steel plate warehouse is too far from the slipways. The first and second alternatives renovate zone 5 shop, carpenter shop, pipe and boiler shop and repair slipways. The two alternatives have steel plate warehouse as well as the addition of two material handling equipment mobile crane and forklift. The second alternative re-locates new machine shop near the slip ways for better material handling and time consuming. The second alternative is the best alternative in terms of economically feasible, good flow of material and perfect of technical term and the most number of ship repairs. Then it can be improved capacity amount 1.43 times and docking time can be reduced from average 33 days to 27 days.